The Role of the Village and Community Empowerment Service in the Development of Village Owned Enterprises (BUMDes) in North Labuhanbatu Regency - Luki Bakti Kusuma; Sirojuzilam; Erlina (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This research aims to find out the role of community and village empowerment agencies in the development of BUMDes in North Labuhanbatu Regency. As an office that handles about villages, community and village empowerment agencies have the task of carrying out training, coaching, and mentoring to the development of BUMDes. The formulation of this research problem is "whether the role of training, coaching and mentoring affects bumdes development in North Labuhanbatu Regency. In this study, data was collected through questionnaire methods of 74 BUMDes administrators to find out respondents' responses to each variable. Then an analysis of the data obtained in the form of validity and rehabilitation tests, classical assumption tests, multiple regression analysis, simultaneous hypothesis tests, partial hypothesis tests and coefficients of determination. The results of this study are: partial test that the variables of training, coaching and mentoring have a positive and significant effect on the development of BUMDes, while simultaneous tests that the variables of training, coaching and mentoring together have a significant effect on the development of BUMDes in North Labuhanbatu Regency.